Executive Committee Minutes 2011-12-08 - Academic Senate:::::::::
GE Unit Policy approved for Senate agenda. Proctor Policy for off-campus tests referred to EPC. Resolution Regarding Shared Governance, the Statewide Senate Budget and the Leadership of Chancellor Reed approved for Senate agenda. Information Item: Academic Calendars 2012 – 2016 referred back to EPC. Disruptive Student Behavior Policy approved for Senate agenda.